Rethinking Quality Science Education for Climate Action: Transdisciplinary Education for Transformative Learning and Engagement - Kubisch, Susanne; Krimm, Hanna; Liebhaber, Nina; Oberauer, Karin; Deisenrieder, Veronika; Parth, Sandra; Frick, Melanie; Stötter, Johann; Keller, Lars (Frontiers in Education, 2022)
Latest findings of the IPCC highlight the fact that there is an urgent need for climate action on both individual and societal levels, because political regulations and technical advances just would not be enough to counter climate change. Acknowledging young people’s role as present and future decision-makers, their engagement is absolutely imperative in order to achieve Sustainable Development Goal 13, “Climate Action.” Therefore, new methods of teaching and learning are necessary, and they need to encourage transformative learning, which, it is assumed, will lay foundations for transformative engagement. Research in the field of science education credits scientific literacy vision III as fostering transformative learning and engagement. In this study, transdisciplinary education is analyzed as a promising concept that enables exchange of knowledge, experiences, and perspectives between students and scientific partners while they jointly complete research on real-world issues. A quantitative analysis capturing scientific literacy and transformative engagement for climate action of Austrian and German secondary school students (N = 162) is carried out alongside a literature review. This study reveals that the didactical concept of transdisciplinary education notably contributes to the implementation of scientific literacy vision III as well as vision II. According to the results, the three visions of scientific literacy are predictors for transformative engagement for climate action, assuming to be preceded by a transformative learning process. These encouraging findings need to be replicated by further scholars in other contexts.